Β-N-methylamino-l-alanine (BMAA) uptake by the animal model, Daphnia magna and subsequent oxidative stress. (15th June 2015) - Esterhuizen-Londt, Maranda; Wiegand, Claudia; Downing, Tim G.
Abstract: β-N-methylamino-l -alanine (BMAA), produced by cyanobacteria, is a neurotoxin implicated in Amyotrophic lateral sclerosis/Parkinsonism dementia complex (ALS/PDC). BMAA concentrations in cyanobacteria are lower than those thought to be necessary to result in neurological damage thus bioaccumulation or biomagnification is required to achieve concentrations able to cause neurodegeneration. Many cyanobacteria produce BMAA and uptake routes into the food web require examination. In this study we investigate the uptake of BMAA by adult phytoplanktivorus Daphnia magna via exposure to dissolved pure BMAA and BMAA containing cyanobacteria, as well as the subsequent oxidative stress response in the daphnia. Free BMAA and protein-associated BMAA were quantified by LC-MS/MS. Dissolved BMAA was taken up and was found as free BMAA in D. magna. No protein-associated BMAA was detected in D. magna after a 24-h exposure period. No BMAA was detectable in D. magna after exposure to BMAA containing cyanobacteria. BMAA inhibited the oxidative stress defence and biotransformation enzymes within 24-h exposure in the tested Daphnia and could therefore impair the oxidant status and the capability of detoxifying other substances in D. magna . Highlights: β- N -methylamino-l -alanine (BMAA) is taken up by Daphnia magna . BMAA is distributed between the free and protein associated forms in Daphnia magna . BMAA causes oxidative stress in Daphnia magna .